Pengaruh Metode Pengawetan Terhadap Kualitas Telur Ayam Konsumsi - Anif Mukaromah Wati; Eka Nurwahyuni; Ardyah Ramadhina Irsanti Putri; Rifa’i Rifa’i; Wuwun Risvita; Purna Pria Atmaja (CV. Komunitas Dunia Peternakan, 2024)
Chicken eggs are a food commodity with high interest and demand in society. Chicken eggs contain complete nutrients needed by the human body, but chicken eggs cannot be stored for long periods. Therefore, this research aims to find the best egg preservation method so that eggs can be stored without changing the important composition of the egg. The materials used are fresh chicken eggs, hot water, and limestone. The method used is preserving eggs with various media: (P0) eggs without preservation, (P1) preserving with limestone, and (P2) preserving eggs by dipping in hot water. Each egg was stored for 7 days at room temperature. The results showed that storing eggs for 7 days using various preservation methods did not significantly affect (P>0.05) of the values of shell thickness, specific gravity, egg cleanliness, and egg texture. This research suggests that storing raw eggs does not require preservation if the eggs are only stored for 7 days. It is best to store it for more than 7 days.